NASCENT ENTREPRENEUR: A SYSTEMATIC REVIEW AND FUTURE RESEARCH DIRECTION - Panjaitan, Roymon (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2022)
The growth of new entrepreneurs becomes a benchmark of entrepreneurial spirit to be independent. The performance of MSMEs still has a number of problems in entrepreneurs first explaining the growth intentions of new business teams with greater family ties. The method used in this study is to collect a number of article literature from reputable journal sources Q1 to Q2. Data collection is done by prisma method which is then data dioalh using Watase software and article clustering using Vos Viewer. Literature searches based on articles published from 2011 – 2021 based on titles, keywords and abstracts. The findings from data sources obtained that the improvement in business planning achieved from nascent entrepreneurs can be improved through institutional strength. The practical implication of these findings is that institutional forces will always be able to excel at measuring the sustainability of innovation performance especially in the context of nascent entrepreneurs. While theoretically strengthening that the institutional strength of the adoption of institutional theory and resource advantage theory of competition to improve the sustainability of MSME performance.